Cylindrical micelles of a POSS amphiphilic dendrimer as nano-reactors for polymerization. Issue 7 (6th February 2018) - Weng, Jing-Ting; Yeh, Tso-Fan; Samuel, Ashok Zachariah; Huang, Yi-Fan; Sie, Jyun-Hao; Wu, Kuan-Yi; Peng, Chi-How; Hamaguchi, Hiro-o; Wang, Chien-Lung
Abstract : A low-generation amphiphilic dendrimer is applied as a nano-reactor for polymerization for the first time. Abstract : A low generation amphiphilic dendrimer, POSS-AD, which has a POSS core and eight amphiphilic arms, was synthesized and used as a nano-reactor to produce well-defined polymer nano-cylinders. Confirmed by small-angle X-ray scattering (SAXS), Raman and NMR spectrometry, monodispersed cylindrical micelles that contain a hydrophilic cavity with a diameter of 2.09 nm and a length of 4.26 nm were produced via co-assemblingPOSS-AD with hydrophilic liquids, such as H2 O and HEMA in hydrophobic solvents. Taking theHEMA /POSS-AD cylindrical micelles as nano-reactors, polymerization of HEMA within the micelles results in polymer nano-cylinders (POSS-AD NPs ) with a diameter of 2.24 nm and a length of 5.02 nm. The study confirmed that despite the inability to maintain specific shape in solution, low generation dendrimers form well-defined nano-containers or nano-reactors, which relies on co-assembling with hydrophilic guest molecules. These nano-reactors are robust enough to maintain their shape during the polymerization of the guest molecules. Polymer nano-cylinders with dimensions less than 10 nm can thus be produced from theHEMA /POSS-AD micelles. Since the chemical structure of low-generation dendrimers and the contents of the co-assembled nano-reactors can be easily adjusted, the concept holds the potential for the further developments of low-generation amphiphilic dendrimers.